Ultrafast Regenerating Spent LiCoO2 Lithium‐Ion Batteries into Bifunctional Electrodes for Rechargeable Zn‐Air Batteries. Issue 1 (14th January 2022) - Yang, Changan; Jin, Zhiwei; Zhang, Xun; Zheng, Xuerong; He, Xuanmeng
Abstract: The ever‐increasing use of lithium‐ion batteries (LIB) results in piles of spent batteries, which threats the environment and the supply chain of strategic metals. Developing sustainable recycling strategies for the cathode of spent LIB can bring about promising environmental and economic benefits. In this work, we present an ultrafast high temperature shock process for regenerating typical LiCoO2 (LCO) spent cathodes into the carbon layer/Co3 O4 composite (C/CO). The nanosized Co3 O4 provides large active sties exposure, while the graphitized carbon layer can potentially enhance the electronic conductivity towards oxygen evolution and oxygen reduction (OER and ORR) catalysis. Benefiting from the enhanced active sties exposure, electronic conductivity, and the synergistic effect between the two domains, the C/CO composite shows efficient bifunctional (OER and ORR) electrocatalytic properties. The OER overpotential (at 10 mA cm −2 ) and ORR on‐set potential reach 245 mV and 0.90 V, respectively. Moreover, the aqueous rechargeable Zn‐air batteries using C/CO composite as air cathodes display high specific capacity (698 mAh g −1 ), power density (131 mW cm −2 ), and as well as cycling stability. This work provides a waste to treasure way that is eco‐friendly, low‐cost, and ultrafast for regenerating the spent LIB for further applications in energy storage systems. Abstract : Recycling batteries : The used LiCoO2 cathodes of lithium‐ion batteries were regenerated into C/Co3 O4 composite by applying the high temperature shock treatment, which is ultrafast and easy for large‐scale application. The as obtained C/Co3 O4 displays bifunctional electrocatalytic activity and durability towards oxygen evolution and oxygen reduction reactions, which enabled the use as cathodes in Zn‐air batteries and display remarkable energy density and long‐term durability performance.